In an Inuit community, climate change has impacted emotional health and connection to the land - Cunsolo Willox, A.; Harper, S.L.; Ford, J.D.; Landman, K.; Houle, K.; Edge, V.L.; the Rigolet Inuit Community Government; Institute for Community Engaged Scholarship (2013)
This summary is a project of the Institute for Community Engaged Scholarship (ICES) at the University of Guelph, with project partners: the Catalyst Centre, SPARK Program at the University of Guelph, and Knowledge Mobilization Unit at York University. This project is part of the Pan-Canadian Research Impact Network. http://csahs.uoguelph.ca/pps/Clear_Research In the Inuit community of Rigolet, Nunatsiavut, Labrador, the environmental effects of climate change include changing weather and ice conditions and shifts in wildlife and vegetation patterns. When residents are unable to carry out traditional “on-the-land” activities, their connection to the land and emotional well-being are negatively impacted. Project support by Agri-Food and Rural Link, Mobilizing Agri-food and Rural Research Knowledge. A program of the OMAFRA-U of G Partnership. http://www.uoguelph.ca/research/omafra/partnership/KTT_and_IP.shtml